Profile Of Critical Thinking Errors Of Junior High School Students Based On Facione's Theory In Solving Problems On SLETV Material - Janna Sri Bina Br Barus; Makmuri Makmuri; Vera Maya Santi (Universitas Islam Sultan Agung, 2026)
This study aims to describe the profile of mathematical critical thinking errors among junior high school students, based on the components of Facione's Theory (Interpretation, Analysis, Evaluation, and Inference), in the context of solving Systems of Linear Equations in Two Variables (SLETV) problems. Specifically, this study cross-mapped Facione's cognitive failures with observed procedural errors, analysing them using the Newman Error Analysis framework (Reading, Understanding, Transformation, Process Skills, and Final Answer Writing). This study uses a qualitative method. This study found that students' critical thinking skills were generally low, with 42.05% in the low category. The highest cognitive failure point was located in the Analysis, Evaluation, and Inference domain. Triangulation analysis showed that weaknesses in Facione's Analysis Skills were the leading cause of the high frequency of Newman Transformation Errors, reflecting students' inability to model contextual problems as mathematical models. This study provides a more precise diagnostic basis for designing targeted learning interventions to optimise students' higher-order cognitive skills.Keywords: critical thinking; indicators Facione; procedural errors; SLETV.